Financing choices of firms in EU accession countiries - Eugene Nivorozhkin (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
The paper presents evidence of actual and target capital structures of firms in five EU accession countries of Central and Eastern Europe and the former Soviet Union (Bulgaria, the Czech Republic, Poland, Romania and Estonia).We consider the financial constraints of private companies and compare the level of indebtedness and the determinants firms choices of capital structure in selected EU accession countries and EU countries.A dynamic non-linear adjustment model is adopted to explicitly model the adjustment of a firm s leverage to a target leverage.
URN:NBN:fi:bof-201408072050
Keywords: 330